AL-ADL SEBAGAI UNSUR HUKUM EKONOMI ISLAM PADA IMPLEMENTASI KEBIJAKAN TAX AMNESTY DI TERNATE - Murtiadi Awaluddin; Bahrul Ulum Rusydi; Muslimin Kara; Elvi Syahria Maznawati (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2020)
Tax Amnesty is a momentum for the government in addition to attracting funds or assets of Indonesian citizens both inside and outside of the country that have not been reported by the taxpayer, and indirectly could provide income to state revenues from the tax sector. The purpose of this study is to identify tax policies regarding Tax Amnesty in terms of al-‘Adl. The research used was field research (descriptive qualitative field research). This research using phenomenology research. Data collection methods obtained through observation, interviews and documentation. The location in this study is in Ternate city. The results showed that Tax Amnesty gives rights to each owner through the Tax Amnesty facility including the elimination of the tax that should be owed, the elimination of administrative sanctions and criminal sanctions in the field of taxation. Another benefit gained is making individual and corporate taxpayers to be more transparent in conducting tax governance in accordingg tax laws.